Remembering Essentials - Stuart E. Cohen (Oz, 1990)
A counterrevolution in architecture has taken place. This counterrevolution, a reaction to modernism, reestablished the belief that architectural forms have meaning, and that meaning can never reside solely in visual or spatial order but depends as well on memory, association, and learning...